The Cultivation of Bone Marrow Mesenchymal Stem Cells Derived from Patients with High Altitude Polycythemia - Zheng, J; Guo, N; Xi, Y; Li, H-Q; Zhang, H; Ji, L-H; Cui, S; Li, Z-Q (Cellular and Molecular Biology, 2015)
The aim of this study was to isolate and culture bone marrow mesenchymal stem cells (MSCs) from patients with high altitude polycythemia (HAPC) in order to provide a foundation for further exploration of their biological characteristics. MSCs were isolated and cultured from 10 HAPC patients and 10 healthy controls by using a density gradient centrifugation and an adherent screening method. The morphous of MSCs were observed under an inverted microscope, and its surface antigens were determined using flow cytometry. The growth of the MSCs was also detected to evaluate its proliferation. Bone marrow mononuclear cells were isolated from the bone marrow using a density gradient centrifugation, and they were cultured in vitro. The bone marrow MSCs were successfully isolated and cultured, which presented as fusiform and adherent cells. The MSCs in both groups expressed CD90,CD44,CD29,CD105, CD106, CD146, CD166,Stro-1 and CD13, but they did not express CD45, CD4,CD8,CD19,CD20,CD80,CD14,CD3,CD34 or HLA-DR (P>0.05). The bone marrow MSCs from HAPC patients had a higher proliferation than the bone marrow MSCs from the healthy controls (P<0.01). The bone marrow MSCs from HAPC patients can be effectively cultured in vitro.